HOW CAN THE EXISTENCE OF COSTUMARY LAW PROTECT THE WATER PRESERVATION IN THE TRADITIONAL VILLAGE CAU BELAYU (TABANAN)? - Wijaya, Made Hendra; Sutrisni, Komang (Yustisia, 2018)
This study aims to analyze and formulate strategies for solving problems arising in the future towards the existence of natural attractions Pengempu Waterfall related to prevention of land use conversion in the tourist area of Pengempu Waterfall in the traditional village of Cau Belayu. Pengempu waterfall located in the area of Cau Belayu traditional village, Tabanan Regency, Bali Province is a new natural tourism area in the region. Besides having natural beauty that can be used as a tourist place, the Pengempu waterfall area is also a sacred area by Hindus to perform prayer activities, meditation and activities related to the spiritual. To preserve the existence of the Pengempu waterfall area so that it is not damaged by the negative impacts caused by tourism activities in the area, it is necessary to have customary law to protect the area of Pengempu waterfalls, because the existence of customary law by Balinese is very important for traditional life in Bali to organize the physical condition of the region and managing the social conditions of the community. The legal approach used in this study is an approach to the concept of legal pluralism. From the results of research that has been carried out, it was found that the existence of customary law to protect the area of Pengempu waterfall to touch the beliefs of the surrounding community in managing the Pengempu waterfall area to maintain the Pengempu waterfall area so that its sustainability has sufficiently dominant power.